Geographic Information System (GIS) in Offshore Pipeline Route Selection: Past, Present, and Future - Dano Umar, Lawal (Espaces Marx, 2013)

(untitled)
The merits of Geographic Information System (GIS) as an effective and versatile analytical tool have enhanced its acceptability as a route selection tool for oil and gas pipelines. Proper pipeline route selection using GIS has numerous benefits including minimizing pipe failures and negative environmental impacts which could be caused by accidental oil leakages. Hence more operators are utilizing the technique, especially for onshore pipeline routing projects. With attention and activities rapidly expanding from onshore to ultra-deep water offshore oil exploration and transportation, it is pertinent to extend the GIS spatial decision making procedure to the offshore domain. The study of offshore pipeline corridor and route selection using GIS and/or Spatial Decision Support System (SDSS) is a relatively new research field. This contrasts sharply with the use of GIS in onshore routing projects which have several case study reports in the literature. The dearth of open access reference materials on offshore pipeline route selection using GIS makes it challenging for students and academic researchers to conduct further research on this vital field. Therefore a comprehensive study will likely provide valuable information on the current efforts of academics in this field and offer possible leads for further research. Consequently, this paper examines and discusses various offshore routing projects in the past and present, with special attention on GIS application. Limitations of GIS in multi-criteria and multi-participant decision making tasks such as offshore pipeline route selection are also discussed. Suggestions on the enhancement on accuracy and reliability of the decision system are proffered. It is hoped that this paper will serve as a valuable catalog of the subject matter and stimulate further research in this relatively nascent field thereby facilitating environmentally safe offshore pipeline routing operations.